End of the Peasantry The Rural Labor Movement in Northeast Brazil, 1961-1988. - Pereira, Anthony W. (Pitt Latin American Ser., 1997)
"Study of emerging rural labor politics in the sugar zone of Pernambuco under military rule shows how popular movements contribute to both democratization and social change. Work is well-researched, sensitive to theory and history, and emphasizes ongoing changes in economic structure"--Handbook of Latin American Studies, v. 57.